2018
DOI: 10.1183/23120541.00079-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional fatigue in pulmonary hypertension: prevalence, severity and predictors

Abstract: Pulmonary hypertension is a potentially fatal disease. Despite pharmacological advances in pulmonary hypertension, fatigue remains common in patients with pulmonary hypertension.A convenience sample of 120 participants at an international patient conference completed the Multidimensional Fatigue Inventory (MFI)-20 scale. Data on New York Heart Association Functional Class, body mass index, oxygen use and medication type/use were also collected.There was a high prevalence of “severe” to “very severe” fatigue fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
3
Order By: Relevance
“…With the development of the disease, it can cause emotional and psychological fluctuations and obstacles in patients and clinically manifests as anxiety and depression. Studies suggested that targeted psychological intervention and psychological counseling for PH patients during treatment can remarkably improve the psychological state of patients and can increase the 5-year survival rate of patients [ 19 ]. In this research, no substantial difference was found in the SAR and SDS scores between the two groups of patients before treatment ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the disease, it can cause emotional and psychological fluctuations and obstacles in patients and clinically manifests as anxiety and depression. Studies suggested that targeted psychological intervention and psychological counseling for PH patients during treatment can remarkably improve the psychological state of patients and can increase the 5-year survival rate of patients [ 19 ]. In this research, no substantial difference was found in the SAR and SDS scores between the two groups of patients before treatment ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It comprises five subscales (General Fatigue, Mental Fatigue, Physical Fatigue, Reduced Activity, and Reduced Motivation), each with four items (two positively and two negatively worded items). The sum of the respective items generates scores for different dimensions, with scores categorized as indicating mild (5)(6)(7)(8), moderate (9-12), severe (13)(14)(15)(16), and very severe (17)(18)(19)(20) fatigue [15]. The total score is the sum of the five-dimensional fatigue scores, and ranges from 20 to 80, where > 60 indicates severe fatigue [14].…”
Section: Multidimensional Fatigue Inventory-20mentioning
confidence: 99%
“…A higher score indicates more fatigue. Severe fatigue is considered present for a dimension if the dimension score is >12 [30]. The total score is the sum of the ve-dimensional fatigue scores, and ranges from 20 to 100, where > 60 indicates severe total fatigue [31].…”
Section: Assessment Of Patient-reported Outcomesmentioning
confidence: 99%